2018
DOI: 10.1093/ajcn/nqy029
|View full text |Cite
|
Sign up to set email alerts
|

Dietary acid load and bone turnover during long-duration spaceflight and bed rest

Abstract: Long-term lowering of NEAP by increasing vegetable and fruit intake may protect against changes in loss of bone mineral content during spaceflight when adequate calcium is consumed, particularly if resistive exercise is not being performed. This trial was registered at clinicaltrials.gov as NCT01713634.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 52 publications
0
26
0
Order By: Relevance
“…Articles included for meta-analysis. We selected 25 articles for meta-analysis, including 12 studies that reported bone density measures before and less than a week after a spaceflight 1,14-23 , 14 studies that contained data on biochemical bone markers [24][25][26][27][28][29][30][31][32][33][34][35][36] , and one study that reported both 37 . The final dataset contained data for~189 astronauts (the number is approximate due to remaining uncertainty in astronaut identification), with bone density measurements and biochemical bone markers available for~148 and~124 astronauts, respectively.…”
Section: Publications On Bone Health In Astronautsmentioning
confidence: 99%
“…Articles included for meta-analysis. We selected 25 articles for meta-analysis, including 12 studies that reported bone density measures before and less than a week after a spaceflight 1,14-23 , 14 studies that contained data on biochemical bone markers [24][25][26][27][28][29][30][31][32][33][34][35][36] , and one study that reported both 37 . The final dataset contained data for~189 astronauts (the number is approximate due to remaining uncertainty in astronaut identification), with bone density measurements and biochemical bone markers available for~148 and~124 astronauts, respectively.…”
Section: Publications On Bone Health In Astronautsmentioning
confidence: 99%
“…Our findings will be useful to investigators conducting clinical or epidemiologic studies that examine potential relationships between the dietdependent acid-base load and human health and disease, 14 exercise performance, 25 or space flight applications. 15 In this study, we used dietary equations to estimate NEAP and found that a number of these calculations accurately predicted their equivalent biochemical measure. In line with previous reports, we found that NEAP R accurately estimated NEAP, 7,16 and for the first time it was observed that NEAP L did as well.…”
Section: Discussionmentioning
confidence: 97%
“…[11][12][13] Clinical and epidemiologic studies routinely rely on estimates of the diet-dependent acid-base load to investigate potential relationships to human health and disease. 14,15 However, a limited number of studies have evaluated the accuracy and precision of estimates of PRAL, NEAP, and their contributors. The accuracy of a measurement is how close a result comes to the true value.…”
mentioning
confidence: 99%
“…The mechanism of the effect of protein and sodium on bone are likely similar, with both contributing to the acidogenic potential of the diet, leading to bone dissolution 91 , 92 . This effect was recently documented in a diet and bone health study on ISS, where the acidogenic potential of the diet correlated with post-flight bone losses 93 . The data from terrestrial research, along with the more limited spaceflight research, clearly identifies nutrition as important in maintenance of bone health and in the mitigation of bone loss.…”
Section: Inadequate Food and Nutritionmentioning
confidence: 96%